Community Understanding of Obligations as a Recipient of PKH Assistance in the Perspective of Islamic Law - Halim, Syaflin; Desminar, Desminar; Mursal, Mursal; Yanti, Elma Rida; Delina, Ros (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
Understanding the obligations of PKH recipients helps the community understand that the assistance received must be used wisely and follow the program's objectives. Communities that understand the importance of good management will be more likely to use the assistance to improve family welfare, such as meeting basic needs, getting proper education, or developing economic skills. This study delved into the community's comprehension of the obligations of PKH recipients within the framework of Islamic law. Employing qualitative research methods, data collection encompassed in-depth interviews, observations, and documentation. Analysis indicated that most PKH beneficiaries grasp their responsibilities and strive to adhere to governmental directives. However, the involvement of religious leaders, though minimal, predominantly entails disseminating general religious messages. Specific initiatives to educate beneficiaries on their obligations within Islamic law are noticeably absent. Nevertheless, the PKH program aligns with the principles of maqashid al-shari'ah, safeguarding core aspects of faith, health, education, and property. Facilitating access to essential services fosters the well-being and advancement of marginalized individuals.